Malawi : Accounting and Auditing - World Bank (Washington, DC, 2012)
This report is based on the findings of a review of accounting and auditing standards and practices in Malawi's corporate sector. The review exercise focused mainly on the strengths and weaknesses of the institutional framework that supports the corporate financial reporting system in the country; a review of Government accounting and auditing practices is outside the scope of this report. This report provides policy recommendations to improve accounting and auditing practices, including strengthening enforcement mechanisms to ensure compliance with accounting and auditing requirements. The key policy recommendations include: 1) Reviewing the Companies Act to provide for up-to-date requirements for financial reporting, and to ensure that there is room/flexibility to incorporate updates as they arise; 2) Reviewing the Public Accountants and Auditors Act to strengthen the regulatory functions of the Malawi Accountants Board (MAB), and reorganizing MAB into an effective independent oversight institution; 3) Putting in place arrangements to require public interest entities to apply IFRS for financial reporting, and to adopt simplified financial reporting requirements for SMEs in Malawi; 4) Enhancing the technical capacity of the professional accountancy body so that it can better support practitioners and institute the required international standards; and 5) Supporting the leading education and training institutions-Department of Accountancy in the University of Malawi and Malawi College of Accountancy-with teaching materials and faculty development, so that they can feed the market with quality graduates and can conduct research for developing the profession in line with up-to-date international practice.